2019
DOI: 10.1177/0047287519863883
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Place Attachment on Social Distance: Examining Mediating Effects of Emotional Solidarity and the Moderating Role of Interaction

Abstract: Building on common identity theory and intergroup contact theory, this study sought to further understanding of people–place relationships by developing a holistic theoretical model to scrutinize place attachment as an antecedent of social distance, mediated by emotional solidarity and moderated by frequency of contact between tourists and residents. Visitor data analyzed with SEM revealed that place dependence is a significant predictor of social distance given it affects affinity positively and avoidance neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 106 publications
(191 reference statements)
5
104
2
2
Order By: Relevance
“…Drawing on the mere exposure and the contact theories, and building on previous works that have either conceptually supported the prominent role local residents play in shaping tourists' destination image and experience, or established links between frequency of interaction tourists develop with locals and their emotional bonding (Aleshinloye et al 2019), the aim of this research was to test the capacity of local resident-tourist and tourism employee-tourist interactions to predict tourists' cognitive, affective and conative image, an aspect that has been largely ignored thus far. The analysis of the findings collected in two studies, one with 353 tourists who visited Kavala, Greece, and a second one with 397 tourists who visited Thasos Island, Greece, revealed that all nine hypothesis were confirmed, except H9 across both studies, and H5 in the second study; while in the first study H8 was confirmed but in the Please cite as: Stylidis, D. (2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on the mere exposure and the contact theories, and building on previous works that have either conceptually supported the prominent role local residents play in shaping tourists' destination image and experience, or established links between frequency of interaction tourists develop with locals and their emotional bonding (Aleshinloye et al 2019), the aim of this research was to test the capacity of local resident-tourist and tourism employee-tourist interactions to predict tourists' cognitive, affective and conative image, an aspect that has been largely ignored thus far. The analysis of the findings collected in two studies, one with 353 tourists who visited Kavala, Greece, and a second one with 397 tourists who visited Thasos Island, Greece, revealed that all nine hypothesis were confirmed, except H9 across both studies, and H5 in the second study; while in the first study H8 was confirmed but in the Please cite as: Stylidis, D. (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous research has conceptualized resident-tourist interactions through interaction frequency (Aleshinloye et al 2019) rather than interaction quality, with researchers calling for more theory-guided quantitative assessment of interaction quality between the tourists and residents of the host communities to better understand relationships (Kirillova et al 2015). In response to such calls, this research further validated a range of items to facilitate the measurement of interaction quality; and separated tourists' interactions with residents from those with tourism employees.…”
Section: Theoretical Contributionmentioning
confidence: 97%
See 1 more Smart Citation
“…The positive trends observed in the increase in cultural tourism together with the profile of tourists interested in cultural heritage are linked to a need to revitalize the cultural heritage sector [42]. In this sense, it is important to take into account the profile of the tourist, as it has been shown that their sociodemographic characteristics can define not only cognitive and affective responses, but also behavioral responses [9]. For example, gender is known to influence information processing strategies [43], while the image of the destination is influenced by age, income, gender, race, nationality and education [44][45][46][47].…”
Section: Tourist Satisfaction and Sociodemographic Characteristics Ofmentioning
confidence: 99%
“…An essential element that can be enjoyed as part of a tourist activity is the experiences that result from the tourist coming into contact with the culture of a specific place, more specifically with the local heritage [7]; in many cases, this refers to the local archeology [8]. To a great extent, the success of a tourist destination depends on the interactions between visitors and local residents [9]. In this sense, an especially important contribution of local residents is when they offer a cultural interchange with visitors who are eager to learn about the heritage of the place.…”
Section: Introductionmentioning
confidence: 99%